2016
DOI: 10.1016/j.yhbeh.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Gestational hormone profiles predict human maternal behavior at 1-year postpartum

Abstract: In many non-human species, including primates, gestational reproductive hormones play an essential role in the onset of maternal motivation and behaviors. We investigated the associations between prepartum estradiol and progesterone and maternal behavior at 1-year postpartumin 177 women. Blood was obtained at five gestational time points and an index of quality of maternal care was determined using a well-validated mother-child interaction protocol. Women who exhibited higher quality maternal care at 1-year po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 98 publications
1
29
0
Order By: Relevance
“…Study designs involving children conceived by in vitro fertilization who were not genetically related to their mothers, research on monozygotic twins who differ as to whether they share a placenta or not, as well as studies of synthetic glucocorticoid administration provide strong evidence that the fetal environment contributes to subsequent child development beyond effects of genetics (Davis et al, 2013; Jacobs et al, 2001b; Lewis et al, 2011; Melnick et al, 1978). Further, although aspects of the postnatal environment such as maternal depression and SES do not account for the observed association, we cannot rule out the possibility that postnatal experiences, including maternal behavior, may contribute to our finding (Glynn et al, 2016). We assessed plasma maternal cortisol because it is strongly correlated with fetal cortisol concentrations (Gitau et al, 1998).…”
Section: Discussionmentioning
confidence: 83%
“…Study designs involving children conceived by in vitro fertilization who were not genetically related to their mothers, research on monozygotic twins who differ as to whether they share a placenta or not, as well as studies of synthetic glucocorticoid administration provide strong evidence that the fetal environment contributes to subsequent child development beyond effects of genetics (Davis et al, 2013; Jacobs et al, 2001b; Lewis et al, 2011; Melnick et al, 1978). Further, although aspects of the postnatal environment such as maternal depression and SES do not account for the observed association, we cannot rule out the possibility that postnatal experiences, including maternal behavior, may contribute to our finding (Glynn et al, 2016). We assessed plasma maternal cortisol because it is strongly correlated with fetal cortisol concentrations (Gitau et al, 1998).…”
Section: Discussionmentioning
confidence: 83%
“…Serotonin is a neurotransmitter implicated in the pathophysiology of depression and a target of many anti-depressant therapies (44). Recent research has demonstrated that fetal sex modi es the association between reproductive hormone pro les across pregnancy and maternal behavior during the postpartum period (45), providing evidence that the fetus may in uence maternal neurobiology with lasting effects. Other research has reported sex-differential levels of reproductive hormones during pregnancy in maternal serum (22) and amniotic uid (46); however, these ndings are not consistent across studies, with some groups detecting no sex-related differences (46).…”
Section: Discussionmentioning
confidence: 99%
“…Other evidence suggests that other hormones, like prolactin and oxytocin (see Gordon, Zagoory-Sharon, Leckman, & Feldman, 2010), play a role in paternal behavior similar to the role these hormones play in maternal behavior (e.g., Uvnäs-Mobcrg, Widström, Nissen, & Björvell, 1990). Furthermore, maternal behavior is associated (p. 436) with estradiol and progesterone, and their ratio, during gestation (e.g., Glynn, Davis, Sandman, & Goldberg, 2016), but their influence in male paternal behavior is unexplored in humans. The independent and interdependent effects of these hormones on parenting and other social behaviors, including social bond paradoxes (i.e., the seemingly contradictory activating function of certain hormones when applied to different circumstances, such as nurturing vs. infant-defense parenting behaviors; see Witczak, Simmons, & Bales, this volume), deserves additional attention.…”
Section: Reproductive Behaviormentioning
confidence: 99%